E-inclusion in Early French Immersion Classrooms: Using Technologies to Support Inclusive Practices That Meet the Needs of All Learners - Pellerin, Martine (Canadian Journal of Education/Revue canadienne de l’éducation, 2013)
The paper discusses a 2-year study that investigated the role of the use of digital technologies in implementing inclusive instructional practices in EFI classrooms. In particular, the paper presents how the use of digital technologies can play a role in the adoption of differentiated and inclusive instructional strategies based on the multiple intelligence theory (Gardner, 1997) and on Universal Design Learning principles (UDL; Cast, 2011). Following the notion of e-inclusion, the use of digital technologies becomes intertwined with effective differentiated and inclusive instructional strategies that support, scaffold, and enhance the learning of all learners in the immersive classrooms.